Representation of Patients’ Hand Modulates Fear Reactions of Patients with Spider Phobia in Virtual Reality - Peperkorn, Henrik M.; Diemer, Julia E.; Alpers, Georg W.; Mühlberger, Andreas (Frontiers in Psychology, 2016)
Embodiment (i.e., the involvement of a bodily representation) is thought to be relevant in emotional experiences. Virtual reality (VR) is a capable means of activating phobic fear in patients. The representation of the patient’s body (e.g., the right hand) in VR enhances immersion and increases presence, but its effect on phobic fear is still unknown. We analyzed the influence of the presentation of the participant’s hand in VR on presence and fear responses in 32 women with spider phobia and 32 matched controls. Participants sat in front of a table with an acrylic glass container within reaching distance. During the experiment this setup was concealed by a head-mounted display (HMD). The VR scenario presented via HMD showed the same setup, i.e. a table with an acrylic glass container. Participants were randomly assigned to one of two experimental groups. In one group, fear responses were triggered by fear-relevant visual input in VR (virtual spider in the virtual acrylic glass container), while information about a real but unseen neutral control animal (living snake in the acrylic glass container) was given. The second group received fear-relevant information of the real but unseen situation (living spider in the acrylic glass container), but visual input was kept neutral VR (virtual snake in the virtual acrylic glass container). Participants were instructed to touch the acrylic glass container with their right hand in 20 consecutive trials. Visibility of the hand was varied randomly in a within-subjects design. We found for all participants that visibility of the participant’s hand increased presence independently of the fear trigger. However, in patients, the influence of the virtual hand on fear depended on the fear trigger. When fear was triggered perceptually, i.e., by a virtual spider, the virtual hand increased fear. When fear was triggered by information about a real spider, the virtual hand had no effect on fear. Our results shed light on the significance of different fear triggers (visual, conceptual) in interaction with body representations.